2022
DOI: 10.2478/emj-2022-0023
|View full text |Cite
|
Sign up to set email alerts
|

Selected contextual factors and entrepreneurial intentions of students on the example of Poland

Abstract: The article analyses the influence of contextual variables on students’ entrepreneurial intentions. The research seeks to extend previous findings concerning the impact of various contextual factors on entrepreneurial intentions. The main focus was on public policy, business environment and education as the contextual traits. The study answers the following questions: What role do contextual variables play in the formation of the entrepreneurial intention of young people? What factors comprise a latent variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…In addition, they are more aware that this will allow them to satisfy their needs and have a better quality of life. The results presented by Galleguillos-Cortés et al, 2019, Kobylińska & Ryciuk, 2022, Valencia-Arias et al, 2022, Romero et al, 2021, López et al, 2021 the factors found to be associated with entrepreneurial behavior propose to: demographic (age and gender), contextual (educational, environmental and cultural aspects) and personality characteristics (autonomy, self-efficacy, motivation and risk decision). As for biological factors, marital status (single, married and cohabiting) and those with children, they were found to be associated with entrepreneurial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are more aware that this will allow them to satisfy their needs and have a better quality of life. The results presented by Galleguillos-Cortés et al, 2019, Kobylińska & Ryciuk, 2022, Valencia-Arias et al, 2022, Romero et al, 2021, López et al, 2021 the factors found to be associated with entrepreneurial behavior propose to: demographic (age and gender), contextual (educational, environmental and cultural aspects) and personality characteristics (autonomy, self-efficacy, motivation and risk decision). As for biological factors, marital status (single, married and cohabiting) and those with children, they were found to be associated with entrepreneurial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Schawarz et al [24] found that general attitudes, entrepreneurship, perceptions of the university environment and regional infrastructure significantly influenced students' interest in entrepreneurship. Contextual factors, such as business policies, programmes and infrastructure, have also been identified as important in creating a favourable business climate in a country [8]. Furthermore, the entrepreneurial environment has a direct impact on the ease of starting and managing entrepreneurial projects, which in turn influences entrepreneurial intentions [25].…”
Section: Business Environment University Training In Entrepreneurship...mentioning
confidence: 99%
“…Similarly, both a country's business environment and entrepreneurship education programmes can influence the intention to start a business [7]. In the case of the entrepreneurial environment, factors such as weak institutional environments, supportive infrastructure and favourable entrepreneurial climates may have an impact on students' entrepreneurial intentions [8]. In turn, university training in entrepreneurship promotes proactivity, innovation and creativity, which in turn influence entrepreneurial intention [9].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the profile of the entrepreneur and the role in organisations as entrepreneurial leaders reveals that there is a close correlation between entrepreneurship and the exploration of opportunities, which the entrepreneurial leader bases on adaptability to change, innovation and risk-taking [59,61]. Entrepreneurial learning has been affected by COVID-19 as it created a physical gap between the learner and the educator [62]. According to [63], the creation of a model of entrepreneurship education for the post-COVID-19 era should have already started.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The SMEs that are properly managed and led gain superior business performance as well as a sustainable competitive advantage [65]. Entrepreneurial leadership has been defined as the extent to which leaders portray entrepreneurial attributes [62]. According to [68], organisational effectiveness is dependent on entrepreneurial attributes inherent in the workforce.…”
Section: Entrepreneurship Leadership and Entrepreneurial Intentionmentioning
confidence: 99%